Addition and multiplication probabilistic arithmetic operation execution error estimation - Сапожников, Николай Евгеньевич; Моисеев, Дмитрий Владимирович; Бейнер, Петр Сергеевич; Бейнер, Надежда Валерьевна (Eastern-European Journal of Enterprise Technologies, 2013)
The most important efficiency component characteristics of information-measuring systems used in nuclear engineering for radiation and gas monitoring, environmental protection and ecological monitoring are survivability, reliability, accuracy while the original information presentation, ability to operate in real time mode, equipment cost, designing cost, production and operation costs. Probabilistic information representation form corresponds to all these characteristics. It is necessary to ensure the implementation of the reforms within the permitted tolerances. This article is devoted to the addition and multiplication probabilistic calculation theoretical errors estimation. The main value of the paper is providing the ground to the choice of the number of statistical tests, which determines the maximum value of the absolute error. The article reveals the factors influencing the accuracy of addition and multiplication probabilistic arithmetic calculations, the number of statistical tests, distribution law of auxiliary random signals, position of converted values within the dynamic range and probabilistic conversion method being among these factors